Refined insights into Africa's plant-soil diversity interplay - Ndiye M. Kebonye; Pegah Khosravani; Zibanani Seletlo; Thomas Scholten (Environmental and Sustainability Indicators)
Plant and soil diversity are intrinsically linked. Yet differences in environmental drivers influencing their coexistence across large areas at high spatial resolution remain largely understudied, partly due to the common focus on each ecosystem component separately. Here, we investigate for the first time the pan-African interplay between plant and soil diversity at the spatial resolution of 250 m/pixel using n = 17,000 observations coupled with the integration of machine learning and interpretable statistical models. We find that different environmental drivers, such as slope, mean annual temperature, and groundwater depth, not only uniquely shape this interplay but also contribute to its heterogeneous wall-to-wall spatial distribution across the continent. The equal magnitude of the reciprocal effects between these two ecosystem components, plant and soil diversity, suggests fully connected interactions among environmental drivers, operating simultaneously in a complex biogeographic system. Taken together, our findings shed light on the fine-scale interplay between continental plant and soil diversity, providing critical knowledge for a detailed understanding of terrestrial ecosystem functioning to ensure targeted monitoring to support life. Furthermore, we underpin the dual conservation of African plants and soils under highly variable environmental conditions from deserts to tropical forests.